Effects of exercise on mGluR-mediated glutamatergic transmission in the striatum of hemiparkinsonian rats. (13th July 2019) - Shi, Kaixuan; Liu, Xiaoli; Hou, Lijuan; Qiao, Decai; Lin, Xiangming
Highlights: The dopamine depletion induced excessive glutamatergic transmission in striatum is a leading cause of PD. Exercise started after dopamine depletion could not exert neuroprotective effects on the dopamine system in PD rats. Exercise increased mGluR2/3 and inhibited mGluR5 expression which might contribute to attenuating glutamate levels. mGluR-mediated modulation of glutamatergic transmission in striatum might be partly related to the improvement of the motor. Abstract: Hyperexcitability in the corticostriatal glutamatergic pathway may have a pivotal role in the pathogenesis of Parkinson's disease (PD). Metabotropic glutamate receptors (mGluRs) modulate glutamate transmission by both pre- and postsynaptic mechanisms, making them attractive targets for modifying pathological changes in the corticostriatal pathway. Exercise reportedly alleviates motor dysfunction and induced neuroplasticity in glutamatergic transmission. Here, the mGluR-mediated plasticity mechanism underlying behavioral improvement by exercise intervention was investigated. The experimental models were prepared by 6-hydroxydopamine injection into the right medial forebrain bundle. The models were evaluated with the apomorphine-induced rotation test. Starting 2 weeks postoperatively, exercise intervention was applied to the PD + Ex group for 4 weeks. The exercise-intervention effects on locomotor behavior, glutamate levels, and mGluR (mGluR2/3 and mGluR5) expression in hemiparkinsonian rats were investigated. The results showed that hemiparkinsonian rats have a significant increase in extracellular glutamate levels in the lesioned-lateral striatum. MGluR2/3 protein expression was reduced while mGluR5 protein expression was increased in the striatum. Notably, treadmill exercise markedly reversed these abnormal changes in the corticostriatal glutamate system and promoted motor performance in PD rats. These findings suggest that mGluR-mediated glutamatergic transmission in the corticostriatal pathway may serve as an attractive target for exercise-induced neuroplasticity in hemiparkinsonian rats.